2020
DOI: 10.1136/bmjopen-2019-032240
|View full text |Cite|
|
Sign up to set email alerts
|

Association of magnesium intake with type 2 diabetes and total stroke: an updated systematic review and meta-analysis

Abstract: ObjectiveThe detailed associations between type 2 diabetes (T2D) and total stroke and magnesium intake as well as the dose–response trend should be updated in a timely manner.DesignSystematic review and meta-analyses.Data sourcesPubMed, Embase, Cochrane Library, Web of Science and ClinicalTrials.gov were rigorously searched from inception to 15 March 2019.Eligibility criteriaProspective cohort studies investigating these two diseases were included.Data synthesisRelative risk (RR) and 95% CI in random effects m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 74 publications
1
42
2
4
Order By: Relevance
“…Type 2 diabetes (T2D) is often associated with altered Mg 2+ homeostasis and Mg 2+ intake is inversely associated with the risk of T2D in a dose-response manner [ 79 , 80 ]. Epidemiologic studies have shown a high prevalence of hypomagnesemia in subjects with T2D [ 81 , 82 ]. Mg 2+ depletion in patients with T2D is mainly caused by a low intake and an increased urinary loss of Mg 2+ , probably resulting from impaired renal function [ 82 ].…”
Section: Mg 2+ In Type 2 Diabetesmentioning
confidence: 99%
“…Type 2 diabetes (T2D) is often associated with altered Mg 2+ homeostasis and Mg 2+ intake is inversely associated with the risk of T2D in a dose-response manner [ 79 , 80 ]. Epidemiologic studies have shown a high prevalence of hypomagnesemia in subjects with T2D [ 81 , 82 ]. Mg 2+ depletion in patients with T2D is mainly caused by a low intake and an increased urinary loss of Mg 2+ , probably resulting from impaired renal function [ 82 ].…”
Section: Mg 2+ In Type 2 Diabetesmentioning
confidence: 99%
“…A significant inverse correlation between Mg intake and the risk for diabetes has been reported [ 20 , 21 ]. Moreover, recent systematic reviews and metanalyses associate hypomagnesemia with the diagnosis and progression of type 1 and 2 diabetes [ 22 , 23 ].…”
Section: A Glimpse Of the Relation Between Mg Intake And Diseasesmentioning
confidence: 99%
“…Cardiovascular disease (CVD) is one of the most common morbidities and the leading cause of death worldwide [1,2]. In addition to traditional risk factors of CVD, such as physical inactivity, tobacco use, hypertension, hypercholesterolemia, obesity and diabetes, magnesium deficiency gained interest during recent years as a potentially modifiable risk factor of CVD [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%